EDUKASI DAN PELATIHAN DATA SCIENCE UNTUK ANALISIS DATA KESEHATAN DALAM MENDUKUNG MASYARAKAT SEHAT DI KOTA PADANG PANJANG - Januardi Nasir; Yasha Langitta Setiawan; Gustri Efendi; Lido Sabda Lesmana (PUAN INDONESIA, 2026)
The development of information technology has brought significant changes to various areas of life, including healthcare. One rapidly developing technology is data science, a discipline that utilizes data processing, statistics, and computational techniques to generate useful information to support decision-making. In healthcare, data science can be used to analyze health data, identify disease patterns, support disease prevention programs, and improve the quality of public health services. However, public understanding and skills in utilizing data science for health data analysis are still relatively limited. Therefore, a Community Service (PKM) activity themed "Data Science Education and Training for Health Data Analysis to Support a Healthy Community in Padang Panjang City" was implemented to improve public literacy and competency in utilizing data technology for healthcare.The activity implementation method included observation and identification of participant needs, program planning, delivery of educational materials, training in the use of RapidMiner software, practical health data analysis, and mentoring and evaluation of the activity. The materials provided covered basic data science concepts, data processing stages, data visualization, and the application of health data analysis using case studies relevant to community conditions. The results of the activity showed that participants gained increased knowledge and skills in understanding Data Science concepts and were able to perform simple health data analysis using RapidMiner. The high level of participant enthusiasm during the training demonstrated that this activity provided tangible benefits and was relevant to community needs. Overall, this activity successfully increased community capacity in utilizing health data as a basis for decision-making and supported the creation of a healthier, smarter, and data-driven society in Padang Panjang City.